2023
DOI: 10.1186/s12903-023-03193-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mechanical properties of different polyetheretherketone endodontic post systems: an in vitro study

Abstract: Background Survival of endodontically treated teeth depends on an efficient restoration of the missing tooth structure. Objectives This study aimed to investigate the mechanical properties of different endodontic post systems. Materials and methods Human permanent maxillary central incisors (no.=58) were decoronated and root-filled. The specimens with prepared root canals were randomly divided into Gro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Core-posts made of PEEK were also tested in vitro in recent studies [39,40]. Sugano et al [40] prepared experimental specimens using extracted bovine mandibular incisors without ferrule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Core-posts made of PEEK were also tested in vitro in recent studies [39,40]. Sugano et al [40] prepared experimental specimens using extracted bovine mandibular incisors without ferrule.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the maximum load to fracture, the researchers concluded that glass fiber post, glass fiber post in glass fiber sleeve, and PEEK post in glass fiber sleeve showed a higher fracture load when compared with other groups and therefore were recommended in cases with flared root canals. Ahmad et al [39] carried out similar tests using 58 human permanent maxillary central incisors divided into two groups: prefabricated PEEK post plus composite core and PEEK custom-made post-core. The specimens were submitted to a pullout resistance test or fracture strength test after restoration with IPS e-max CAD crown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our protocol slightly differs with those retrieved in previous publications, as we chose to perform a tissue preparation before sealing the posts in order to create a ferule effect on the tooth. This parameter was also designed in only 5 publications of the 22 published since 2020 [53,55,[57][58][59]. It may also be worth highlighting one of the parameters that varies greatly between the different studies, namely the type of support on which the tests have been carried out.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be worth highlighting one of the parameters that varies greatly between the different studies, namely the type of support on which the tests have been carried out. Without taking into account numerical simulation analyses, in vitro tests have been carried out on natural human teeth [56,59,60], bovine teeth [55,57,61] or artificial supports [62,63], which can significantly change the results obtained. Finally, the last parameters that may influence the differences observed between the studies concern the nature of the assembling biomaterial or the post's size.…”
Section: Discussionmentioning
confidence: 99%